A la recherche de la traduction parfaite : discours des traducteurs et censeurs portugais de la seconde moitié du 18e siècle - Cláudio Denipoti (Nuevo mundo - Mundos Nuevos, 2017)
During the 18th Century, the Portuguese scholars and men of letters made an effort to translate a large quantity of books – of science, literature and religion – trying to give the Republic of Letters a national vernacular and orthodoxy. This text deals with the idealizations translators and censors made of such translations in the last decades of the Century, when this effort was strongest.